Flipping the Classroom: The Indonesian Evidence-Based Analysis of Flipped Learning Impact on English Language Learners' Engagement and Academic Performance - Prasetya, Rizky Eka (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The content and scope of this paper are to provide an evidence-based analysis of the impact of flipped Learning on English language learners' engagement and academic performance. The objective of the paper is to explore the efficacy of flipped learning in enriching student engagement and academic performance. The study implemented a convergent parallel design mixed-methods approach to analyze the impact of flipped learning. The empirical studies revealed that flipped learning significantly positively impacts student engagement compared to traditional teaching methods, with a moderate effect size (d=0.56). Similarly, the analysis of exam scores indicated that students in the flipped learning group outperformed their peers in the traditional teaching group, with a small to medium effect size (d=0.35). The thematic analysis of the interview data revealed that contextual factors such as course content, student characteristics, and instructional strategies play a significant role in the effectiveness of flipped learning. The findings suggest that flipped learning is a functional approach to enhancing student engagement and academic performance. The results of this study provide empirical evidence for the benefits of flipped learning and support its implementation in various educational contexts. This study's findings exposed that English lecturers can use flipped learning as an effective instructional strategy to enhance student engagement and academic performance. The study emphasizes the need for English lecturers to consider contextual factors when designing and implementing flipped learning activities to optimize their effectiveness.